The relationship between an increasing Barnacle Goose Branta leucopsis population and the number and size of colonies in Svalbard - Prestrud, Paal; Black, Jeffrey M; Owen, Myrfyn (Wildfowl, 1989)
This paper documents the current numbers and distribution of Barnacle Goose colonies in Svalbard, Norway. Using the data from the literature and current censuses we investigate the possibility that the recent increase in numbers in this population is slowing due to a limited number of nesting places and conclude that nesting space per se is not limiting. More likely density dependent effects operate through the interaction between the geese and their food supply on the nesting and brood rearing areas.